Pengaruh Penambahan Semen dan Abu Sekam Padi Terhadap Kepadatan Tanah dan Daya Dukung Tanah Lempung - Yelrian Gelong; Irwan Lie Keng Wong; Ika Apriyani (Paulus Civil Engineering Journal, 2023)
The basic principle of earthworks for roads is to be able to provide the space needed for traffic movement safely and smoothly, the subgrade as the foundation for the foundation of the road body must be able to support the traffic load that is channeled through the pavement without significant deformation. The purpose of this study was to determine the physical properties of the soil from the Muunloe sub-district, to determine the effect of the addition of cement and rice husk ash on the density of clay soil and to review the effect of the addition of cement and rice husk ash on the carrying capacity of clay soil by testing the DCP. Based on the AASHTO classification, soils originating from Moncongloe District, Maros Regency are clay soils with moderate plasticity and included in the classification group A-7-5 (17). The carrying capacity of the clay soils used in this study reached 11.17%, while for soils varied with 5% cement by 16.46%, for variations of 5% cement and 5% rice husk ash obtained CBR values of 14.79%, for variations of 5% cement and 10% rice husk ash by 11.17% and 12.91% for soil varied by 5% cement and 15% rice husk ash, the highest CBR value increase was in the 5% cement variation, which was 5.24% of the original soil.